A visão de professores e gestores escolares sobre finalidades educativas escolares e as proposições oficiais: repercussão nas políticas e ações de formação continuada na escola - Sentoma, Thays Roberta de Abreu Gonzaga (2025)
The present research was born in the context of the group called CEPId, at PUC-SP and is anchored in the theoretical framework of quantitative and qualitative approaches and its general objective is to analyse the aims of school education (ASE) expressed by professionals from nursery and primary schools (teachers, pedagogical coordinators, principals and vice-principals), to contrast them with those stated in official federal, state and municipal documents, and to identify how they reverberate in the policies and actions of continuing education in Santo André Municipal Network.Our thesis is that it is necessary to discuss and to identify the desired aims of school education in Santo André municipality´s schools, from the perspective of the professionals who work in this network, in comparison with the proposals of the educational policies in force there, given that they are essential for the interpretation and the implementation of changes towards the school we want and need. The theoretical framework was based on the following authors: Lenoir et al., 2016; Libâneo, 2012; 2016a; 2016b; 2016c; 2019, 2023; Gatti and Barreto, 2009; Pereira et al, 2018; Imbernón, 2010, 2019, 2024; Nóvoa, 1992, 2020; Placco, 2010; Placco and Souza, 2015, 2019 and the official guidance documents for Brazilian education: LDB (Lei nº 9394/96), Plano Nacional de Educação – PNE (2014-2024), DCNB (2013), PME (2015-2025) and Documento Curricular da Secretaria Municipal de Santo André (2019). Data was produced using a questionnaire and discussion groups. The data analysis was inspired by the proposal of Prose Analysis (André, 1983) and (Sigalla, Placco, 2022) and gave rise to five categories for analysis.The main findings highlighted are: (1) dissent over the conception of the ASE; (2) the main aim attributed to the school, related to humanisation and welcoming; (3) the overflow of the aims of school education; (4) the neoliberal view of the guiding documents of educational policies, focused on the curriculum of results, by means of external evaluations; (5) continuing training policy focused on the appropriation of the ten competences of the BNCC; (6) the challenges of training centred on the school, with the CP as a training teacher (with an excess of functional attributions).This analysis has allowed us to understand that there is a marked and contradictory disagreement between the perspectives or positions of the professionals, the official documents and what the authors propose on the subject. Thus, debating the ASE, educational policies and the training of education professionals has become indispensable and urgent, as reflection and taking a position on them can be a means of overcoming the current situation in which we find ourselves, in which educational reforms are tied to the economic interests of neoliberalism